Multi-omics analysis of organ-specific hormone distribution and molecular regulatory mechanisms in Cinnamomum burmanni - Zhang, Tanhang; Yao, Jun; Zhang, Qian; Cai, Yanling; Lian, Huiming; Wang, Minghuai; Chen, Jielian; Zhang, Huihui; Hou, Chen (Frontiers in Plant Science, 2025)
Cinnamomum burmanni serves as a principal arboreal species utilized for the extraction of essential oils, and its foliage and branches contain a wide array of terpenoid compounds. These compounds are extensively utilized in the cosmetic and pharmaceutical sectors. However, the organ-specific distribution of phytohormones and the underlying molecular regulatory mechanisms in C. burmanni have not been fully elucidated. Consequently, this study presents the first comprehensive metabolomic, transcriptomic, and full-length transcriptomic analyses aimed at systematically elucidating the organ-specific hormone distribution and molecular regulatory networks within the leaves, stems, and roots of borneol-type C. burmanni. The research identified 70 significantly differential hormones, including 32 cytokinin (CTK)-related hormones, 19 auxin-related hormones, and seven gibberellin (GA)-related hormones, uncovering distinct organ-specific patterns: indole-3-acetic acid (IAA) predominantly accumulated in leaves, while GA and CTK were highly expressed in stems. Additionally, 812 differentially expressed genes (DEGs) were identified among different organs, including 50 hormone signaling-related DEGs pinpointed via weighted gene co-expression network analysis (WGCNA). Further investigations indicated that several putative transcription factors (TFs), including ARF, bHLH (PIF3/4), GRAS (DELLA), G2-like (GLK/KAN1/2/HH2O/APL/FT), and ARR-B, may constitute a core regulatory module that mediates hormone-dependent growth, development, and terpenoid biosynthesis. This study establishes the first multi-omics-driven hormonal interaction network framework for the molecular breeding of C. burmanni while developing a gene editing target atlas to elucidate synergistic regulatory mechanisms underlying medicinal secondary metabolite biosynthesis.